PENTINGNYA PEMAHAMAN BIOMEKANIKA BAGI GURU PJOK DALAM MENINGKATKAN KUALITAS PEMBELAJARAN GERAK - Ahmad Mursyidin; Suci Muliya; Muh. Amin; Taufiqurrahman; Ferdi (STKIP Subang, 2026)
Understanding biomechanics is a fundamental competency that Physical Education, Sport, and Health (PJOK) teachers must possess in order to effectively facilitate quality movement learning. This article examines the importance of biomechanical knowledge for PJOK teachers, covering key concepts such as Newton's laws of motion, levers, center of gravity, momentum, and projectile motion, as well as their practical application in designing, evaluating, and correcting students' movement patterns. A qualitative literature review approach was employed, drawing on relevant theoretical and empirical studies published within the last five years. The findings indicate that PJOK teachers with strong biomechanical understanding are better equipped to provide accurate movement feedback, prevent sports injuries, and adapt instruction to suit diverse student needs. Integration of biomechanics into pedagogical practice enhances student achievement in fundamental movement skills and fosters safer, more effective physical education experiences. Implications for teacher professional development programs and pre-service teacher education curricula are also discussed.